FAKTOR-FAKTOR YANG MEMPENGARUHI PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN BERBASIS AKRUAL - Darma Putra, I Wayan Gde Yogiswara; Ariyanto, Dodik (E-Jurnal Akuntansi; Vol 13 No 1 (2015), 2015)
This study aims to determine the effect of the quality of human resources, communications, organizational commitment, and leadership style to the readiness of the application of the accrual-based government accounting standards. The analytical tool used is multiple linear regression. The sample was all SKPDs Badung which includes department heads, secretaries, and the finance department staff. These results indicate that the variable quality of human resources, communications, organizational commitment, and leadership style has positive influence on the readiness of the application of the accrual-based government accounting standards
Keywords: Accrual Based Accounting Standards Administration.